2013
DOI: 10.1002/eqe.2379
|View full text |Cite
|
Sign up to set email alerts
|

Seismic vibration control of building structures with multiple tuned mass damper floors integrated

Abstract: SUMMARY Floor isolation system (FIS) achieving very small floor accelerations has been used to ensure human comfortability or protect important equipments in buildings. Tuned mass damper (TMD) with large mass ratios has been demonstrated to be robust with respect to the changes in structural properties. This paper presents the concept of a TMD floor vibration control system, which takes advantages of both the FIS and TMD. Such a system is called ‘TMD floor system’ herein. The TMD floor system (TMDFS) in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…Moon [37] had shown that the multiple tuned mass dampers (MTMDs) distributed vertically along the entire structure improved effectiveness of the control of response of the high-rise buildings. Lately, Xiang and Nishitani [58] reported that the MTMDs are effective for multi-mode control of the low-rise buildings with closely spaced frequencies under earthquake ground excitations. Effectiveness of the distributed tuned mass dampers (d-TMDs) to control the across wind vibration of 76-storey benchmark building was studied by Elias and Matsagar [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moon [37] had shown that the multiple tuned mass dampers (MTMDs) distributed vertically along the entire structure improved effectiveness of the control of response of the high-rise buildings. Lately, Xiang and Nishitani [58] reported that the MTMDs are effective for multi-mode control of the low-rise buildings with closely spaced frequencies under earthquake ground excitations. Effectiveness of the distributed tuned mass dampers (d-TMDs) to control the across wind vibration of 76-storey benchmark building was studied by Elias and Matsagar [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for the fully-distributed actuation scheme AS3 in Figure 2c, the list of actuation positions is AP 3 = [1, 3,5,7,9,11,13,15,17,19], and we obtain the control location matrix …”
Section: Building Modelmentioning
confidence: 99%
“…In addition, an LMI formulation for robust non-fragile static controllers with sampled-data feedback information is obtained in [26] using a dissipativity approach. (a) Actuation Scheme 1 (b) Actuation Scheme 2 3,5,7,9,11,13,15,17,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of passive control, much progress has been accomplished, especially in base isolation and di erent types of mechanical energy dissipaters, such as single Tuned Mass Damper (TMD) [9], double TMD [10], and multiple TMD [11][12][13][14]. The optimization of TMD parameters has been studied in structural control for many years and di erent methods have been proposed for optimal design of TMDs for linear structures, including selecting the parameters of a TMD for the undamped structure under sinusoidal excitation [15], minimization of the Root-Mean-Square (RMS) of the main structure's displacement or acceleration under white noise excitation [16], maximization of the e ective damping of the structure incorporating the TMD [17], and minimization of the di erence between the damping values of the rst two modes of the structure-TMD coupled system [18].…”
Section: Introductionmentioning
confidence: 99%